The flowering, Pollination and Hybridization of Groundnuts (Arachis hypogaea L.) - Lim, E. S.; Gumpil, J. S. (1984)
The flowering pattern, emasculation and pollination of loc.ally grown groundnuts were studied. Flowering generally occurred between 0645 to 0900 h with a half hour delay on dull days. Anther dehiscence occurred itl- the bud about one hour prior to blooming. Pollen tube growth was approximately 1 em per hour and fertilization was estimated to take place 5 to 6 hours after pollination. There was no improvement in pod set following tripping of the flowers although it was found that assisted pollination improved peg formation over natural self-pollination. Emasculations can be carried out either using forceps or suction on the afternoon prior to the day of anthesis without any detrimental effect on the success of cross-pollination. Some cross-combinations and parents were capable of higher success in cross-pollinations than others.